Digestibility of fat sources by growing pigs - De-Fa Li; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1984)
A digestion trial was conducted with 12 crossbred barrows averaging 48 lb to evaluate the digestibility of various fat sources. Fat sources evaluated were soybean oil, a 85% dry fat product composed of animal and vegetable fat, and a 80% dry fat product made by encapsulating choice white grease with casein. The control diet was a 18% crude protein corn-soybean meal diet with 10% cornstarch. Fat sources were added to the basal diet at the expense of cornstarch to supply 8% added fat. A crossover design was used with three pigs per diet in each of two periods. Digestibility of dry matter, energy, ether extract were (P<.05) lower for the diet containing the 85% dry fat product. Nitrogen digestibility and nitrogen retention were reduced also when the 85% dry fat product was fed. These results suggest that the two dry fat products evaluated are markedly different in nutritional value for growing pigs.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Digestibility; Growing pigs